Role of Carbon Quantum Dots in the Development of Herbal-Based Endodontic Irrigation Materials: A Literature Review - Edi Satria; Nevi Yanti; Widi Prasetia (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Background: The irrigation process of root canals plays a significant role in cleaning the root system of microorganisms and dead tissue. However, chemical irrigation materials such as NaOCl often cause side effects such as tissue irritation and toxicity. Therefore, the use of safer and environmentally friendly natural materials has become the focus of recent research. Objective: This study aims to review the development of the use of Carbon Quantum Dots (CQDs) based on natural materials as an alternative for root canal irrigation. Method: The study was conducted by tracing literature from the last five years (2020–2025) through databases such as Google Scholar. Only experimental research that tests the efficacy and characterization of CQDs from herbal extracts was analyzed. Results: CQDs synthesized from plants such as betel leaf, green tea, ginger, and propolis have high antibacterial properties, fluorescence characteristics, and do not damage dentin tissue. These compounds are also effective against resistant bacteria such as E. faecalis and have the potential to be used in photodynamic therapy.Conclusion: Herbal-based CQDs are considered promising as a safe, efficient, and sustainable irrigation agent. However, more clinical trials are needed to prove its efficacy in endodontic practice.